Pathêt: Ruang Bunyi dalam Karawitan Gaya Yogyakarta - Hanggar Budi Prasetya (LP2M ISBI Bandung, 2012)
This research aims to answer a question of why two Javanese gamelan pieces (gending) of differ- ent pathêt (modes) cannot be performed consecutively without grambyangan lead. The data of this research were obtained from in-depth interview and observation of karawitan (gamelan performanc- es), focusing on karawitan training process, wayang performances, and karawitan performances for pleasure or uyon-uyon. Using phenomenology method, it can be concluded that pathêt is a space of sound. Two gamelan pieces having different modes are similar to two gamelan pieces in different spaces. There is a link between spaces that can be opened by the sound of gender or grambyangan. As a space, karawitan has three spaces of sound, i.e. space of pathêt nem, space of pathêt sanga, and space of pathêt manyura. Keywords: gending, pathêt, ruang bunyi, karawitan Jawa.